Child Sexual Abuse in Focus: A Case Study on Case Management in a Selected Local Government Unit in Metro Manila - Algo, Florinor (Asean Social Work Journal, 2024)
This study explores the processes and challenges faced by Local Government Unit (LGU) social workers in the Philippines when managing cases of child sexual abuse (CSA) under a child rights-based framework. It seeks to identify the facilitating and hindering factors that influence the application of case management protocols for CSA survivors, examining the impact of professional, organizational, political, and cultural aspects in a selected LGU in Metro Manila. Employing a mixed-methods approach, data were gathered through a Rapid Assessment Instrument (RAI) survey of 28 LGU social workers, supplemented by qualitative in-depth and key informant interviews with additional stakeholders. Findings indicate that variability in case management practices is influenced by resource limitations, levels of political support, and cultural attitudes toward CSA, underscoring the need for enhanced training, resources, and support at the LGU level.